CHALLENGES OF STUDENTS' ORAL PRESENTATIONS AND THE TEACHER'S ROLE IN ADDRESSING - Mahametova Dilnavoz Botirovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation. This article focuses on the importance of student's oral presentation and difficulties, as well as the role of the teacher in solving them.
Keywords: Keywords: oral speech, difficulties, solution, fear of speech, language learning